Photodegradation of 12-deoxy-13, 16-dioxy phorbol esters in aqueous solution under UV light and natural sunlight. Issue 6 (December 2017) - Kongmany, Santi; Truong, Hoa Thi; Hanh, Le Thi Ngoc; Matsuura, Hiroto; Furuta, Masakazu; Okuda, Shuichi; Imamura, Kiyoshi; Maeda, Yasuaki
Abstract: 12-Deoxy-13, 16-dioxy phorbol esters (PEs) are bio-active and highly toxic compounds that can be found in the seed oil of the Jatropha curcas Linnaeus (JCL) plant. In this report, the photodegradation behaviors of PEs and an isolated J2 component were examined under UV/Vis254–575nm irradiation (power 0.4–120 W/m 2 ) and natural sunlight (maximum power of 800–1100 W/m 2 ) in aqueous solution. The J2 was selectively degraded when it was irradiated with UV254–280nm . The photodegradation of the PEs occurred with first order kinetics, and the rate constants of J2 and PEs under UV254nm irradiation were 1.78 × 10 −2 and 2.41 × 10 −3 s −1, respectively. The rate constant of the PEs under natural sunlight was 1.37 × 10 −3 s −1 . Characterization by high performance liquid chromatography/tandem mass spectrometry revealed that the degradation process was preceded by the isomerization of the conjugated unsaturated diester group of the PEs, followed by disruption of the phorbol skeleton. These results indicate that PEs can be selectively degraded in aqueous solution by UV254–280nm and/or Vis545–575nm irradiation. The aqueous waste streams contaminated with PEs that are generated during biodiesel production could therefore be detoxified by degradation under UV254nm light and natural sunlight.